2007
DOI: 10.1148/radiol.2432060286
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Breast Imaging: Results of a Pilot Study in Women with Abnormal Mammograms

Abstract: Results from EM breast examinations provide statistical evidence of a mean increase in image contrast of 150%-200% between abnormal (benign and malignant) and normal breast tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
236
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(247 citation statements)
references
References 34 publications
7
236
3
1
Order By: Relevance
“…[24][25][26] We have shown that MT has substantial diagnostic potential, especially in the discrimination of breast cancer from other benign abnormalities. 19 This study reported an AUC [area under the receiver operating characteristic (ROC) curve] as high as 0.89 for breast lesions larger than 1 cm 19 which is comparable to diagnostic outcomes for MR. 5 These results are due to the excellent specificity of the MT technique compared with superior sensitivity as in the case of MR. 27,28 Our MT data indicate that the proportional increase in (electrical) permittivity, which has been observed with increasing breast density, 20,29,30 also results in cancer and reflects higher water content in breast disease. However, the threshold change found in cancer (electrical) conductivity occurs because the amount of water in malignancy is sufficient to saturate its local binding sites leading to an increase in unbound water in cancer that is not evident in either dense normal parenchyma or other benign processes in the breast.…”
Section: Introductionmentioning
confidence: 78%
“…[24][25][26] We have shown that MT has substantial diagnostic potential, especially in the discrimination of breast cancer from other benign abnormalities. 19 This study reported an AUC [area under the receiver operating characteristic (ROC) curve] as high as 0.89 for breast lesions larger than 1 cm 19 which is comparable to diagnostic outcomes for MR. 5 These results are due to the excellent specificity of the MT technique compared with superior sensitivity as in the case of MR. 27,28 Our MT data indicate that the proportional increase in (electrical) permittivity, which has been observed with increasing breast density, 20,29,30 also results in cancer and reflects higher water content in breast disease. However, the threshold change found in cancer (electrical) conductivity occurs because the amount of water in malignancy is sufficient to saturate its local binding sites leading to an increase in unbound water in cancer that is not evident in either dense normal parenchyma or other benign processes in the breast.…”
Section: Introductionmentioning
confidence: 78%
“…The imaging with microwaves allows non-destructive evaluation of biological tissues due to the non-ionizing nature of microwaves, since changes in the dielectric properties of tissue can be related to their physiological condition. One of the most promising applications deployed is detection of breast tumors [1][2][3][4]. This is particularly eligible due to the easy approach of the breast for imaging, as well as the breast anatomy where the fatty tissue (with low loss) has a low attenuation impact on the signal.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in breast imaging include frequency domain inverse-scattering approaches, such as those by Meany et al, which have demonstrated successful numerical and phantom results [5,8] and very promising preliminary clinical studies [9,10]. Additionally, Synthetic Aperture Radar (SAR) based techniques such as Tissue Sensing Adaptive Radar (TSAR) [4,11] and Microwave Imaging via Space Time Beamforming (MIST) [12,13] are proposed.…”
Section: Introductionmentioning
confidence: 99%